The "futurist" aesthetics of ISIS. Issue 1 (1st January 2017) - Botz-Bornstein, Thorsten
ABSTRACT: ISIS propaganda differs from that of other (Islamic or non-Islamic) religions or cults as it is not so much concerned with imagination and exotic fantasies but accentuates the maximal exploitation and demonstration of available technology. The Islamic State does not only excel through the extensive use of high-tech weapons, social media, commercial bot, and automated text systems; by putting forward the presence of speeding cars and tanks, mobile phones, and computers, ISIS presents jihad life as connected to modern urban culture. The article shows that the aesthetics of the Islamic State is "futurist" by comparing it with Italian Futurism. Futurism glorified cars, industrial machines, and modern cities while praising violence as a means of leaving behind imitations of the past in order to project itself most efficiently into the future. A profound sense of crisis produces in both Futurism and jihadism a nihilistic attitude toward the present state of society that will be overcome through an exaltation of technology. The futurist project to integrate life and art is paralleled by ISIS's desire to integrate life and religion. In both cases the result is achieved through violence.